“El desarrollo de la Coordinación en los fundamentos técnicos del fútbol en la categoría 10-12 años de la Unidad Educativa Liceo Policial Chimborazo, periodo febrero-agosto 2016.” - Llanga Colcha, Marlon Gabriel (2016)
“DEARROLLO COODINATION IN THE TECHNICAL FOUNDATIONS OF FOOTBALL IN THE CATEGORY 10-12 YEARS LICEO POLICE UNIT EDUCATIONAL CHIMBORAZO, PERIOD FEBRUARY – AUGUST 2016”. This research aimed to determine the development of coordination and its impact on the technical fundamentals of football in the 10- 12 year of age category in Unidad Educativa Liceo Policial Chimborazo by a guide of exercises in order to improve coordination and soccer technical fundamentals for six weeks. For this important research 25 player were evaluated. A pre and post-test were applied for coordination on the stairs, precision ball, and hit driving test ball. The results acquired in the implementation of the exercise guide coordination and technical foundations of football were significant at time of implementation of the post test. The exercises used in this guide and applied training sessions were coordinating, driving and hitting the ball with the foot. It has been concluded that coordination affects within the basic foundations of soccer and improve their lifestyle. Descriptors: ball, coordination, Driving, exercises, ladder, training, grounds, players, guide, test